Hybrid learning of ESP in Agriculture field: Students’ perceptions and learning experiences - Adi, Sugeng Susilo (Universitas Muhammadiyah Sidoarjo, 2023)
This research has the objective of describing the learning perceptions and experiences of students of the Agro Eco Technology Study Program while attending the English for Specific Purposes (ESP) course that is organized with the mode of hybrid learning. The students who became the subject of this research were those who study at the Kediri campus of Universitas Brawijaya. They are freshmen who had previously for two years experienced full online learning while studying in senior high school. This research used a mixed method, meaning applying both quantitative and qualitative approaches. Data are in the form of survey results and of interview results with several related parties, observations, and other relevant documents. Research results indicated that student perceptions regarding ESP learning were that it is able to improve the English language competence of students. Students found that the learning environment of ESP with hybrid learning was interesting, encouraging, enjoyable, accommodating of active participation, and not at all awkward. In addition, the opportunity given by the lecturer to students to show their work orally by uploading videos to a YouTube channel with the ‘everybody is a YouTuber’ program became a point that is perceived as able to encourage the students. They have positive responses about statements on the issues of attitude, of ease, of aspects of benefits, and of English language skills. The Internet connection that is sometimes unstable only became a minor hindrance. HIGHLIGHTS: In hybrid learning, the group of students who learned in the synchronous online class were all actively participating in learning by always turning on their cameras. They were proud when the lecturer compared them to the students of the main campus of Universitas Brawijaya at City of Malang. Students had the opinion that hybrid learning for ESP was conducted in a quite relaxed and not awkward manner. This was even perceived to be easygoing at times. The lecturer initiated the ‘everybody is a YouTuber’ program for the students to take advantage of YouTube to show their oral work for the course in the form of a video recording, for which the link was posted on Google Classroom.